SOSIOLOGI PENDIDIKAN: MEMAHAMI INTERAKSI ANTARA PENDIDIKAN DAN MASYARAKAT - Edi Purwanto; Mukhamad Rifai; Muriyanto (As-Sulthan Journal of Education, 2025)
This research aims to explore the definition and scope of educational sociology as a scientific discipline that studies interactions between education and society. The main focus of this research is to identify various sociological aspects that influence the education system and how education plays a role in forming norms and values in society. The method used in this research is the literature study method. Data was collected through literature studies which included books, scientific articles and other related documents. This approach allows researchers to explore the concepts of educational sociology in depth and understand the social dynamics that influence education. The research results show that educational sociology does not only focus on educational institutions, but also on social, cultural and economic relationships that influence the educational process. In addition, this research identifies several factors such as social stratification, family roles, and media influence as important elements in understanding educational phenomena. Sociology of education functions as a tool for analyzing the challenges faced by the education system, as well as providing insight for improving education policy. With a better understanding of the definition and scope, it is hoped that this research can contribute to the development of the sociology of education and educational practice in society.